2020
DOI: 10.3390/ijms22010261
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Changes of Murine Visceral Fat Exposed to Intermittent Hypoxia at Single Cell Resolution

Abstract: Intermittent hypoxia (IH) is a hallmark of obstructive sleep apnea (OSA) and induces metabolic dysfunction manifesting as inflammation, increased lipolysis and insulin resistance in visceral white adipose tissues (vWAT). However, the cell types and their corresponding transcriptional pathways underlying these functional perturbations are unknown. Here, we applied single nucleus RNA sequencing (snRNA-seq) coupled with aggregate RNA-seq methods to evaluate the cellular heterogeneity in vWAT following IH exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 133 publications
0
3
0
Order By: Relevance
“…To overcome these limitations [31], single-nucleus RNA-sequencing (snRNA-seq) has been employed in studies on tissues composed of diverse cell types, including the brain [33,34], kidney [35][36][37], heart [38], skeletal muscle [39,40], stria vascularis [41], retina [42], liver [43,44], lung [45], or white [46,47] and brown adipose tissue [48,49] obtained from mice or human donors. Here, we report a side-by-side comparison between snRNA-seq and scRNA-seq to validate the robustness of the former as an alternative sequencing strategy.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations [31], single-nucleus RNA-sequencing (snRNA-seq) has been employed in studies on tissues composed of diverse cell types, including the brain [33,34], kidney [35][36][37], heart [38], skeletal muscle [39,40], stria vascularis [41], retina [42], liver [43,44], lung [45], or white [46,47] and brown adipose tissue [48,49] obtained from mice or human donors. Here, we report a side-by-side comparison between snRNA-seq and scRNA-seq to validate the robustness of the former as an alternative sequencing strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that several genetic variants interacted with each other, including MCTP1_rs4290997, KIF7_rs2350480, F2_rs2070850, PEX3_rs223231, TBC1D22A_rs910543, and PLA2G4C_rs7252136. MCTP1 is a marker for macrophage-1, which may have implications for immunity [25]; PEX3 is related to oxidative stress [26]; F2 is linked to diabetic conditions [27]; PLA2G4C plays a role in the hydrolysis of membrane phospholipids, specifically phosphatidylcholine, which can affect inflammation and MetS [28]. TBC1D22A is involved in cellular processes related to intracellular trafficking and the regulation of cellular metabolism, although research in the context of MetS is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there are several scientific research methods and several technologies are being developed. Some emerging research methods can be introduced into the study of adipose tissue, such as the three-dimensional genome of adipocytes and single-cell multi-omics sequencing, to discover more functional genes that play a role in the function of adipose tissue [123][124][125]. In addition, in recent years, tRNA-derived RNA fragments and piRNAs in ncRNAs have also attracted the attention of researchers [126,127], and their roles in adipose tissue are still worthy of our attention and exploration.…”
Section: Discussionmentioning
confidence: 99%